Astronomy for Dummies : 4th Edition - Maran, Stephen P. (John Willey & Sons, 2017)
Do you know the difference between a red giant and a white dwarf? From asteroids to black holes, this easy to understand guide takes you on a grand tour of the universe and shows you how to look up into the night sky and contemplate cosmic wonders.